UPAYA MENINGKATKAN KETERAMPILAN MENYIMAK CERITA RAKYAT DENGAN PENGGUNAAN MEDIA AUDIO VISUAL PADA SISWA KELAS V SDN 2 BALE KECAMATAN TANATOVEA - Gunawan, Gunawan (BAHASANTODEA, 2016)
Based on the problem formula in this research is whether with the using of audio visual media scrutinize ability in folklore can improve and how is audio visual media in improving scrutinize skills learning at fifth grade students at SDN 2 Bale. There is a research method which used is kualitative and kuantitative method, these are rivalry assortment method strategy in descriptive form. The aim of this research is to improve scrutinize ability in folklore or description about the using of audio visual media in improving scrutinize ability. Technique that used by researcher is non structure interview that is free interview and using main instrument and supporting instrument. Main instrument is a researcher and supprting instrument is observation compass, field note, documentation and photos. Result of this research formulated that using audio visual media in indonesian language especially scrutinize in folklore obtained class average is 74,61% and the percentage classical completeness achieve 84,61% with 11 students who complete from 13 students. Result of interview from a teacher in the class, senior teacher and KUPTD education is very thankfull by the using of that media. Students response well to the benefit of audio visual media in indonesian language learning, especially scrutinize in folklore. Factors which show the weakness of audio visual media in learning that is if the school yet achieved electricity and facility of that media had yet by the school. Whereas the positive impact in the using of audio visual media based on theÂ interview result of a teacher in the class, senior teacher, and KUPTD education is very need to developed with the technology developing and learning system which have quality, until not resposibility the students in receiving the material f the subject. Therefore, audio visual learning media is effisien and have benefit for the teacher or student.